Al-nahw al-muyassar = Nahu mudah edisi kemas kini - Mustapai, Mohd Zulhisyam; Mat Zain, Zairul (Telaga Biru Sdn Bhd, 2022)
A book that talks about the basic methods of Arabic grammar explained in Malay, still maintaining the concept of the previous edition with improvements in the updated edition and very suitable for the general public and beginner level Arabic students.